Basic research on postoperative cognitive dysfunction in the past decade: a bibliometric analysis - Wu, Hongwei; Song, Jiannan; Hu, Zhanfei; Li, Haibo; Zhou, Qi; Dai, Congcong; Gao, Yi; Ma, WanLi (Frontiers in Aging Neuroscience, 2025)
ObjectivePostoperative cognitive dysfunction (POCD) is a prevalent complication following anesthesia and surgery that particularly affects elderly patients, and poses significant health risks. In recent years, there has been an increase in basic research on POCD, with a particular focus on its molecular mechanisms, which have become a prominent area of inquiry. However, no bibliometric analysis has been conducted in this field. This study aims to employ bibliometric methods to comprehensively summarize the current status and developmental trends of basic research on POCD, providing new ideas and strategies for future scientific investigations.MethodsRelevant literature published between January 1, 2014, and October 30, 2024, was retrieved from the Web of Science Core Collection. Eligible articles were exported in plain text format. The annual output of published papers and data on authors, countries/institutions, journals, keywords, co-cited journals, and co-cited literature were analyzed and visualized using Microsoft Excel, VOSviewer, and CiteSpace software.ResultsA total of 479 papers from 13 countries were included, with a noticeable upward trend in publications over the past decade, particularly in the last 3 years. A total of 105 core authors published four or more papers, with Professor Zuozhiyi identified as the leading contributor. “The Journal of Neuroinflammation” emerged as the most prolific publication source, while Chinese scholars accounted for the highest number of contributions and Dutch scholars led in citations per article. The University of Virginia was the leading institution for publications. Analysis of research hotspots revealed “neuroinflammation,” “surgery,” “impairment,” “memory,” and “information” as frequently occurring keywords. Notably, “pyroptosis” was identified as a current research hotspot and “synaptic plasticity” as a rapidly emerging term. The top five cited journals were all ranked as Q1 journals, with “Anesthesiology” being the most cited. Within co-cited articles, the “hippocampal CA1 region” represented the largest cluster, and literature on “neuroinflammation” was a key reference in current discussions.ConclusionOver the past decade, basic research on POCD has steadily increased, particularly among Chinese scholars. Bibliometric analysis revealed that the molecular mechanisms underlying POCD are likely crucial focuses of current and future research. This field holds significant potential for further development.